2008
DOI: 10.1246/cl.2008.558
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chiral Recognition of Novel Regioselectively Substituted Amylose Derivatives

Abstract: Two novel amylose derivatives 1a and 1b bearing different substituents at 2-, 3-, and 6-positions of a glucose ring have been successfully synthesized, and their abilities of enantiomer resolution in high-performance liquid chromatography (HPLC) have been evaluated. These derivatives exhibited the ability comparable or better to the commercial amylose-based column, Chiralpak AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 10 publications
1
25
0
Order By: Relevance
“…Finally, the 6‐hydroxyl group was regenerated by the removal of the trityl group in a methanol/HCl mixture and reacted with R 2 NCO to form the corresponding carbamate. It should be pointed out that in this study triphenylmethyl chloride was used instead of 4‐methoxytriphenylmethyl chloride to selectively protect the 6‐hydroxyl group and both of them were effective to protect the 6‐hydroxyl group as trityl ether …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the 6‐hydroxyl group was regenerated by the removal of the trityl group in a methanol/HCl mixture and reacted with R 2 NCO to form the corresponding carbamate. It should be pointed out that in this study triphenylmethyl chloride was used instead of 4‐methoxytriphenylmethyl chloride to selectively protect the 6‐hydroxyl group and both of them were effective to protect the 6‐hydroxyl group as trityl ether …”
Section: Resultsmentioning
confidence: 99%
“…In Table are summarized the chromatographic resolution results of racemates 2 – 9 on 1a – f using a conventional eluent, hexane/2‐propanol (90:10, v /v). Moreover, the data on the commercially available chiral column, Chiralpak AD, utilizing coated amylose tris(3,5‐dimethylphenylcarbamate) as chiral selector, which is regarded as one of the most useful CSPs, are included. Compared with Chiralpak AD, 1a – f showed higher chiral recognition abilities to racemates 2 and 7 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhang et al indicated that Brönsted acidic ILs can be used as a novel catalyst for the efficient acetylation of cellulose to onestep synthesize cellulose acetate with different DS and solubility. [23][24][25] However, the regioselective synthesis of cellulose esters is a complex and challenging work. 14 In physical organic chemistry, investigating the effect of substituents on the aromatic ring on the reaction rate is one of the most important methods to clarify the reaction process of esterication, alcoholysis, hydrolysis, etc.…”
Section: Introductionmentioning
confidence: 99%